2003
DOI: 10.1111/j.1741-3729.2003.00279.x
|View full text |Cite
|
Sign up to set email alerts
|

Military Families Under Stress: Implications for Family Life Education*

Abstract: We provide a summary of the limited research on three uniquely stressful experiences of military families: relocation, separation, and reunion. Using the insights derived from this literature, we identify and discuss interventions to assist and guide military families through these unique events.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
206
1
9

Year Published

2008
2008
2016
2016

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 260 publications
(229 citation statements)
references
References 40 publications
4
206
1
9
Order By: Relevance
“…Plusieurs auteurs soulèvent certaines contradictions qui existent entre les exigences du système familial et l'organisation militaire en tant qu'employeur (Ryan-Wenger, 2001;Drummet, Coleman et Cable, 2003;Harrison, 2006;Harrison, 2002;Harrison et Laliberté, 1997;Darwin et Reich, 2006). L'organisation militaire prône la cohésion des troupes et la primauté des besoins du pays sur ceux des soldats et de leur famille.…”
Section: Conditions Du Travail Militaire Vie De Couple Et Vie Familialeunclassified
See 3 more Smart Citations
“…Plusieurs auteurs soulèvent certaines contradictions qui existent entre les exigences du système familial et l'organisation militaire en tant qu'employeur (Ryan-Wenger, 2001;Drummet, Coleman et Cable, 2003;Harrison, 2006;Harrison, 2002;Harrison et Laliberté, 1997;Darwin et Reich, 2006). L'organisation militaire prône la cohésion des troupes et la primauté des besoins du pays sur ceux des soldats et de leur famille.…”
Section: Conditions Du Travail Militaire Vie De Couple Et Vie Familialeunclassified
“…Inhérents à la carrière militaire, les déploiements constituent un important facteur de stress pour les familles. Durant cette absence, toutes les responsabilités de la maisonnée, l'entretien, les finances, l'éducation, la santé des membres de la famille, sans oublier de possibles soins aux familles étendues, incombent généralement à la mère (Drummet, Coleman et Cable, 2003;Hiew, 1992).…”
Section: Conditions Du Travail Militaire Vie De Couple Et Vie Familialeunclassified
See 2 more Smart Citations
“…Interestingly, 1 study of Navy families, for whom routine 6-month "sea duty" deployments were a way of life for years, indicated that children demonstrated increased responsibility, independence, and confidence compared with their peers without deployment experiences, suggesting that children develop a different and beneficial parent-child relationship with the athome parent. 29 In many nonmilitary situations in which parents are absent for periods of time but not in danger, many children demonstrate resilience and strong coping strategies.…”
Section: Effect Of Wartime Deployment On Children Previous Researchmentioning
confidence: 99%